Strategic Prioritization of IT Projects to Enhance Banking Operations Efficiency - Saribatiara, Saribatiara; Purwanto, Agustinus Hariadi Djoko (International Journal of Indonesian Business Review, 2025)
Purpose – This study aims to develop a strategy for prioritizing information technology (IT) development projects that align with the operational objectives and resource limitations of Bank BRI. Methodology/approach – The research adopts a mixed-methods approach. The Analytical Hierarchy Process (AHP) is employed to determine the priority weight of each IT project based on five key criteria: customer acquisition, service quality, regulatory compliance, product innovation, and operational efficiency. Focus Group Discussions (FGDs) are conducted with key stakeholders to validate findings and identify implementation barriers. Root cause analysis using Why-Why and Fishbone Diagrams is performed to uncover underlying issues in project delays and prioritization gaps. Findings – It was found that projects contributing to increased transactions and customer base receive the highest priority. However, FGD findings reveal that implementation often diverges from analytical priority due to resource constraints, unclear scope, and lack of filtering mechanisms. A set of strategies is proposed to improve project filtering, resource allocation, and inter-unit coordination. Novelty/value – This research introduces an integrated prioritization framework combining AHP with stakeholder validation and root cause analysis, offering a practical approach to IT project governance in banking institutions. The model enhances decision-making beyond weight-based ranking by incorporating real-world constraints and institutional readiness.